2016
DOI: 10.5001/omj.2016.43
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Optic Neuritis and Cervical Cord Schwannoma with Charcot-Marie-Tooth Type 4B1 Disease

Abstract: Charcot-Marie-Tooth neuropathy type 4B1 (CMT4B1) disease is a rare subtype of CMT4 with reported association of facial weakness, vocal cord paresis, chest deformities, and claw hands. We report the unusual occurrence of optic neuritis and cervical cord schwannoma in a male individual with confirmed CMT4B1 disease. Sequencing of the MTMR2 gene revealed a novel nonsense homozygous mutation c.1768C>T (p.Gln590*). The mutation was identified in affected relatives of the proband and a second, apparently unrelated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Compound muscle action potential and motor conduction velocity could be measured only in patient II.3 from family 1 at severely reduced levels (Table 1). In agreement with most previously reported cases of CMT4B1 (Bolino et al, 2000; Houlden et al, 2001; Parman et al, 2004; Verny et al, 2004; Nouioua et al, 2011; Murakami et al, 2013; Scott et al, 2016), our cases were also sired by consanguineous parents.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Compound muscle action potential and motor conduction velocity could be measured only in patient II.3 from family 1 at severely reduced levels (Table 1). In agreement with most previously reported cases of CMT4B1 (Bolino et al, 2000; Houlden et al, 2001; Parman et al, 2004; Verny et al, 2004; Nouioua et al, 2011; Murakami et al, 2013; Scott et al, 2016), our cases were also sired by consanguineous parents.…”
Section: Discussionsupporting
confidence: 93%
“…CMT4B1 is characterized by severe progressive distal and proximal muscular weakness in early childhood, initially starting at the lower limbs, as well as sensory loss and decreased nerve conduction velocity (Quattrone et al, 1996; Bolino et al, 2000; Houlden et al, 2001; Parman et al, 2004; Verny et al, 2004; Nouioua et al, 2011; Scott et al, 2016). We report nine children from four unrelated families with a typical CMT4B1 phenotype of severe early-onset motor and sensory neuropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, truncating variants in this gene have been associated with the pathogenesis of Charcot–Marie–Tooth disease, type 4B3 (MIM# 615284), a rare subtype of this disease; however, the number of reports regarding the pathogenesis of SBF1 ‐related neuropathies is limited. Scott et al (2016) described the co‐occurrence of optic neuritis and cervical cord schwannoma in a 28‐year‐old man with molecularly confirmed Charcot–Marie–Tooth neuropathy (the individual carried an SBF1 homozygous nonsense c.1768C>T [p.Gln590Ter] variant). In this study, we found a total of 10 different SGSM1/SBF1 variants in 9 unrelated individuals (these individuals were not reported to have likely PVs in other schwannomatosis‐predisposing candidate genes), all variants are predicted as deleterious or probably damaging according to SIFT and PolyPhen‐2, respectively, and/or as having a possible effect on splicing (details in Table ).…”
Section: Discussionmentioning
confidence: 99%
“…CMT4B3 has been more recently associated with mutations in the MTMR5/SBF1 gene, but is characterized by different phenotypes with either a pure demyelinating neuropathy with myelin outfoldings or an axonal polyneuropathy complicated by multiple cranial involvement, intellectual disability, microcephaly, and dysmorphic features. All three subtypes are extremely rare, with around 38 CMT4B1, 37 CMT4B2, and 14 CMT4B3 patients described so far, mostly from countries with high frequency of consanguineous marriages …”
mentioning
confidence: 99%